Developing competent managers: The shadow of Hungarian history - Katalin Illes; Bronwen Rees (Journal for East European Management Studies, 2001)
Hungary is deemed to be one of the economies that has successfully undergone the changes and undoubtedly it is undergoing a process of rapid and concentrated change. It is generally considered that Hungary has successfully completed these changes, and is now ready to take its rightful place in the European Union. Despite this, it has been pointed out that Hungarian managers are still lacking in education and training, that there is a lack of innovation, and that there is still a certain resistance to change manifest in the continuance of the black market economy. However, it is optimistically expected that the influx of Western managerial practices will soon put this to rights (Agenda 2000). – – Es heißt, die ungarische Volkswirtschaft zählt zu denen, die sich erfolgreich reformiert haben und es finden noch immer schnelle und konzentrierte Veränderungen statt. Allgemein wird eingeschätzt, dass Ungarn die Herausforderungen der Transformation erfolgreich bewältigt hat und nun bereit ist, seinen berechtigten Platz in der Europäischen Union einzunehmen. Trotzdem wurde argumentiert, dass ungarische Manager noch immer Nachholebedarf in den Bereichen Bildung und Ausbildung haben, dass nicht genügend Innovationen stattfinden und dass es noch immer einen gewissen Widerstand gegen Veränderungen gibt, der sich im fortdauernden Bestehen der Schwarzmarkt-Wirtschaft manifestiert. Es wird jedoch erwartet, dass unter dem Einfluss westlicher Managementpraktiken diese Missstände bald beseitigt werden.
Keywords: 650